Constructing and Preliminary Validation of the School Peace Culture Scale - Eliasa, Eva Imania; Ilfiandra, Ilfiandra; Buchori, Sahril; Suwarjo, Suwarjo; Fakhri, Nurfitriany; Latif, Suciani; Nadhirah, Nadia Auliah (Journal of Educational Science and Technology (EST), 2024)
Educational opportunities are part of the culture of peace, which includes many areas of the community's well-being. This study comes up with a new way to measure school peace culture called the School Peace Culture Scale (SPCS). The researcher made the tool by evaluating it theoretically, checking its content validity, followed by doing a confirmatory study to check its internal and external psychometrics. The people who answered were in charge of or led Vocational High Schools in Makassar. There were 63 of them, 24 men and 39 women. The Winstep Rasch Model tool is used to analyze the data. The SPCS has been carefully checked for validity, and 34 items that are particularly good at measuring factors have been found. The results indicate a reliability value of 0.91 and item reliability of 0.82. The study also proved that the proposed SPCS questionnaire can measure the level of peace in schools. Furthermore, the research has confirmed that the items in the proposed SPCS questionnaire effectively assess the extent to which peace is implemented in schools. These results provide a foundation for further investigation. The questionnaire can help determine the extent to which a peaceful culture has been established in schools. Furthermore, the SPCS concept and questionnaire could be valuable tools for assessing schools that require training in promoting peaceful education.